Analysis of Environmental Literacy among Students at MAN 2 Tuban - A. Farid Rohmatulloh; Vivi Novianti; Mimien Henie Irawati Al Muhdhar (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2026)
This study aimed to analyze the environmental literacy level of students at MAN 2 Tuban based on four aspects: ecological knowledge, cognitive skills, environmental attitudes, and environmental behavior. A quantitative descriptive research design was employed. The sampling technique used was simple random sampling, involving 66 eleventh-grade students as the research sample. Data were collected through tests and surveys. The research instruments consisted of multiple-choice questions to assess ecological knowledge and cognitive skills, and an environmental literacy questionnaire adapted from the Middle School Environmental Literacy Survey to measure students’ environmental attitudes and behavior. The findings indicated that students’ ecological knowledge and cognitive skills were lower than their environmental attitudes and behavior. Overall, 77.27% of students were categorized as having a moderate level of environmental literacy, while 22.73% were categorized as having a high level. The mean scores for each aspect were 57 for ecological knowledge, categorized as fair; 51 for cognitive skills, categorized as fair; 69 for environmental attitudes, categorized as high; and 61 for environmental behavior, categorized as high. These results reveal an imbalance between students’ conceptual understanding and their environmental attitudes and behavioral tendencies. Therefore, learning strategies that place greater emphasis on strengthening cognitive aspects are needed to ensure alignment between students’ knowledge, attitudes, and behavior toward the environment.